WOMEN AND RACISM IN KAMALA HARRIS’ SPEECHES: A CRITICAL DISCOURSE ANALYSIS - TSANI, NOVIA KURNIA; RATNADEWI, DWIJANI (Linguists : Journal of Linguistics and Language Teaching, 2022)
Critical Discourse Analysis is an approach to studying a text to increase the reader's awareness of the meaning behind and the real purpose of the text. Previous studies analyzed texts with a general CDA approach, while this research focuses on a specific topic, namely women and racism. Using Norman Fairclough's three-dimensional critical discourse analysis theory and Van Dijk's sociocognitive approach, this study aims to analyze the types and uses of women's issues and racism, as well as the personal and impersonal motivations behind Kamala Harris' speeches. A total of three speeches and their scripts were selected and categorized based on the indicators of women's issues and racism. This study revealed five types and use of racism issues for women of colour that Kamala Harris raised in her speeches, namely women of colour in the economy, education, civil and society, justice, and health care. Her motivation was a call to take action against women of colour's injustice.